Analysis Community’s Coping Strategies and Local Risk Governance Framework in Relation to Landslide - Heru Setiawan; Nanette C. Kingma; C.J. van Westen (Faculty of Geography, Universitas Gadjah Mada, 2014)
Analysis of people perception and analysis of the coping strategy to landslides are the two elements that are es-sential to determine the level of preparedness of communities to landslides. To know the preparedness of government and other stakeholders in facing landslide, the analysis risk governance framework was required. A survey using questionnaires with random sampling was applied to assess the level of people perception and people coping strategy related to landslide. Analysis of risk governance frame work was done at the district and sub-district level. ἀe study found that people perception related with landslide dominated by high and moderate level. Age and education are two factors that inḀuence the people’s perception to landslide. Local people applied four types coping strategy, which are: economic, structural, social and cultural coping strategy. Totally, 51.6% respondents have high level, 33.3% have moderate level and only 15.1% respondents that have low level of coping strategy. ἀe factors that inḀuence the level of coping strategy are education, income and building type. Analysis of risk governance framework is limited to the three components including stakeholder involvement, risk management and risk communication. Based on the data analysis, the level of stakeholder involvement at the district scope was categorized on the moderate till high and the level of stakeholder involvement at sub-district level was categorized on the high level. Generally, the risk management of Karanganyar was categorized on the moderate level and high level and the risk management in Tawangmangu was categorized on the moderate level. ἀere are some elements must be improved on the risk governance framework, those are data management, the pattern of relationships among stakeholders, increased participation of NGOs, constructed and updated landslide risk map, enhancement of microᴀnance role in helping the com-munity when disaster strikes and dissemination of information about the landslide to the local community.